Association between the triglyceride to high-density lipoprotein cholesterol ratio and type 2 diabetes mellitus in non-alcoholic fatty liver disease - Liya Bian; Ting Tang; Qingwen Yu; Xuhan Tong; Siqi Hu; Yao You; Shenghui Zhang; Hu Wang; Xinyan Fu; Juan Chen; Xingwei Zhang; Mingwei Wang; et al. (Scientific Reports)
Abstract This study evaluated the ability of the triglyceride (TG) to high-density lipoprotein cholesterol (TG/HDL-C) ratio to identify individuals at risk of type 2 diabetes mellitus (T2DM) in the non-alcoholic fatty liver disease (NAFLD) population. We retrospectively studied 4,769 patients with NAFLD from the Affiliated Hospital of Hangzhou Normal University (2020–2023). Binary logistic regression models were used to evaluate the association between the TG/HDL-C ratio and lipid parameters with T2DM. TG/HDL-C ratio was positively associated with T2DM in patients with NAFLD, with an odds ratio (OR) of 2.72 (95% confidence interval, 2.23–3.31, p < 0.001) for T2DM in the highest TG/HDL-C ratio quartile compared with the lowest one after adjusting for known confounders. The OR for the TG/HDL-C ratio had a stronger predictive value than those of TG, total cholesterol, HDL-C, and low-density lipoprotein cholesterol, indicating that the TG/HDL-C ratio could be a better discriminator of T2DM. The TG/HDL-C ratio better identifies potential risks of T2DM in individuals with NAFLD than individual lipid parameters. Therefore, clinicians should pay attention to individuals with high TG and low HDL-C levels during T2DM risk assessment in NAFLD cohorts.